2012
DOI: 10.1158/0008-5472.can-11-3525
|View full text |Cite
|
Sign up to set email alerts
|

Definition of Genetic Events Directing the Development of Distinct Types of Brain Tumors from Postnatal Neural Stem/Progenitor Cells

Abstract: Although brain tumors are classified and treated based upon their histology, the molecular factors involved in the development of various tumor types remain unknown. In this study, we show that the type and order of genetic events directs the development of gliomas, central nervous system primitive neuroectodermal tumors, and atypical teratoid/rhabdoid-like tumors from postnatal mouse neural stem/progenitor cells (NSC/NPC). We found that the overexpression of specific genes led to the development of these thre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 53 publications
1
11
0
Order By: Relevance
“…Hertwig et al (33) has reported that a panel of 7 signature genes can be used in error freely classification of three CNS tumors: glioma, PNET and ATRT. We therefore assessed the expression of this panel of 7 genes in the tumors induced by HRasV12/AKT in combination with Ngn2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hertwig et al (33) has reported that a panel of 7 signature genes can be used in error freely classification of three CNS tumors: glioma, PNET and ATRT. We therefore assessed the expression of this panel of 7 genes in the tumors induced by HRasV12/AKT in combination with Ngn2.…”
Section: Resultsmentioning
confidence: 99%
“…Overwhelming experimental and clinical evidence show that different genetic mutations result in different tumor types including different CNS tumor types (37). For example, Hertwig et al (33) showed that infection of postnatal mouse neural stem cells with viruses containing V12HRAS or c-MYC could result in formation of 3 different tumor types depending upon the combination and sequence in which oncogenes were introduced. Similarly, Jacques et al (38) showed that different combinations of conditional genetic deletions in p53, Rb and PTEN in mouse subventricular zone neural stem cells could induce formation of either PNET or glioma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SMARCB1 loss profoundly activates the transcription factor MYC, resulting in significant upregulation of protein anabolism which can render cells susceptible to disruption of their proteostatic machinery [7,8]. To further investigate the biological mechanisms underlying this finding, we developed Smarcb1-deficient embryonic mosaic mouse models of MRT and found that SMARCB1-deficient cancer cells show profound evidence of endoplasmic reticulum (ER) stress, including ER swelling, reticulophagy, alterations in the ERribosome interfase, and prominent accumulation of cytoplasmic protein aggregates.…”
Section: Targeting Proteostasis and Autophagy In Smarcb1-deficient Mamentioning
confidence: 99%
“…There is experimental evidence supporting both models. For example, 3 distinctly different CNS tumor types can be induced by infection of postnatal mouse neural stem cells with virus containing V12HRAS and c-MYC depending on the combination and sequence in which oncogenes are introduced [ 4 ]. Similarly, RNA interference (RNAi) knock down of NF1 and p53 in GFAP+ or SynI+ cells induces mesenchymal GBM, whereas the same RNAi in Nestin+ cells induced neural GBM[ 5 ].…”
mentioning
confidence: 99%